Proceedings of the International Conference on Chinese Enterprise Research 2007 - Fu, Xiaofang; Tan, Teng-Kee; Teo, Anthony S. C. (World Scientific, 2008)
The International Conference on Chinese Enterprise Research (ICCER) is an annual event organized by the Lien-Chinese Enterprise Research Centre, Nanyang Technological University. Held on 13 and 14 December 2007 at Nanyang Technological University and the Singapore Chinese Chamber of Commerce & Industry respectively, the succeeding ICCER enjoyed immense support from local and international Management scholars, boosting the scale and academic standing of the conference. The conference invited famous keynote speakers, including Professor Zhang Weiying, Dean of Guanghua School of Management, Peking University and Professor Zhao Renwei, former director of the Institute of Economy, Chinese Academy of Social Science. At the same time, attendance also included heads of Nanjing University, Sun Yat-Sen University, Northwest University and Sichuan University's Management and Economics schools, together with research directors and professors of the finest educational institutions. In addition to academic presentations, a panel of prominent economists such as Professor Tan Khee Giap from Nanyang Technological University, Mr Xu Li, General Manager of Industrial and Commercial Bank of China (Singapore) and Mr Jack Niu, Deputy Group Chief Credit Officer, Standard Chartered Bank also deliberated on the topic "Internationalization of Banks in China". The keynote speeches, together with a collection of 25 excellent research papers from the conference are presented to the readers in this proceedings